Time-programmed activation of dual polyprodrugs for synergistic cascade oxidation-chemotherapy. (November 2021) - Liu, Ye; Jiang, Maolin; Tu, Yalan; Wang, Kewei; Zong, Qingyu; Yuan, Youyong
Abstract: Combination therapy using multiple drugs with time-programmed administration is promising for enhanced cancer treatment. However, it is still challenging to achieve time-programmed drug release from a single nanocarrier. Here, dual polyprodrugs of hemicyanine dye (CyNH2 ) and doxorubicin (DOX) are developed to achieve time-programmed prodrug activation for synergistic cascade oxidation therapy and chemotherapy. The polyprodrug NPDOX/Cy, composed of CyNH2, is modified with a glutathione (GSH)-responsive disulfate group, while DOX is modified with a reactive oxygen species (ROS)-response thioketal (TK) group. Upon uptake by cancer cells overexpressing GSH, CyNH2 can be activated quickly and accumulate in the mitochondria to induce mitochondrial damage and ROS upregulation, thus achieving subsequent burst activation of DOX through the ROS-triggered cleavage of the TK linker. The early activation of CyNH2 makes the cancer cells more sensitive to subsequent DOX treatment for a synergistic effect of from oxidation therapy and chemotherapy. Therefore, the polyprodrug with time-programmed drug activation developed in this work provides a promising strategy for synergistic cancer therapy.